FROM READINESS TO RESULTS THE MEDIATING POWER OF DIGITAL MARKETING IN THE RELATIONSHIP BETWEEN SUSTAINABILITY AND SME PERFORMANCE - Dhaula Patta Raya; Sisno Riyoko; Mohamad Rifqy Roosdhani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study aims to examine the effect of sustainability orientation, digital readiness, and entrepreneurial orientation on the marketing performance of small and medium-sized enterprises (SMEs), with digital marketing acting as a mediating variable. The research is grounded in the view that strategic orientations and internal readiness must be effectively translated into digital marketing activities to achieve superior marketing outcomes. A quantitative approach was employed, and data were collected through a survey distributed to SME owners and managers. The collected data were analyzed to assess both direct and indirect relationships among the research variables. The findings reveal that sustainability orientation, digital readiness, and entrepreneurial orientation positively influence marketing performance. Moreover, digital marketing serves as a key mechanism that strengthens the impact of these strategic factors on marketing performance. These results indicate that sustainability values, digital capabilities, and entrepreneurial initiatives generate greater marketing benefits when implemented through effective digital marketing strategies. This study contributes to the literature on SME marketing by highlighting the integrative role of digital marketing in enhancing performance and offers practical insights for SME practitioners and policymakers in developing competitive, digitally driven, and sustainable marketing strategies.